Kallikrein‐related peptidases are activators of the CC chemokine CCL14. Issue 9 (22nd August 2018) - Grünberg, Mario; Quandt, Dagmar; Cynis, Holger; Demuth, Hans‐Ulrich; Kindermann, Andrea; Magdolen, Viktor; Forssmann, Wolf‐Georg; Seliger, Barbara; Mägert, Hans‐Jürgen
Abstract : Chemokine CCL14 is inactive in its proform. Here, we show that inflammation‐ and cancer‐associated kallikrein‐related peptidases KLK5 and KLK8 remove the N‐terminal eight amino acids from the proform thereby converting CCL14 to its active state. Activity of the chemokine is demonstrated by migration of myeloid cells expressing relevant receptors.